"We Never Recovered": The Social Cost of the 1951 New Zealand Waterfront Dispute. (1st May 2015) - Millar, Grace
Abstract : In July 1951, 15, 000 New Zealand watersiders, miners, freezing-workers and seamen returned to work after being locked-out or on strike, but their lives, and the lives of those dependent on their income, did not return to normal. For five months, most workers and their families had had to borrow money and leave bills unpaid in order to survive, and they needed to pay their debts. This article examines the social cost of the 1951 waterfront dispute. It concentrates on strike debt, and the long shadow that debt cast on family and community relationships. This article argues that many of the costs of an industrial dispute are not paid until after it ends, but in contrast to union's collective concern about costs during the dispute, costs after the dispute are privatised and treated as the concern of individual families.